Examining sustainable performance using SEM-FsQCA: The role of TQM, green SCM, and competitive advantage in small and medium enterprises (SMEs) - Ilyas Masudin; Ricco Faris Barraq; Fien Zulfikarijah; Tsiqatun Nasyiah; Dian Palupi Restuputri; Terri Trireksani; Hadrian Geri Djajadikerta (Sustainable Futures)
This study investigates the impacts of total quality management and green supply chain management practices on competitive advantage within the context of sustainability performance in small and medium-sized enterprises. This research uses a quantitative approach with 102 owners of Indonesian small and medium-sized enterprises and applies structural equation modeling and fuzzy-set qualitative comparative analysis to evaluate the relationship among variables. The findings reveal that total quality management and green supply chain management practices individually contribute to sustainability performance in small and medium-sized enterprises. Additionally, competitive advantage emerges as a mediating factor between total quality management and green supply chain management, and sustainability performance. The study underscores the importance of formulating comprehensive strategies that synergistically integrate total quality management and green supply chain management practices to fortify operational efficiency and resilience in the dynamic business landscape. The strong connection between total quality management and sustainability performance in the fuzzy-set qualitative comparative analysis reinforces their collective impact on outcomes, aligning with prior research and highlighting the reliability of this relationship. Furthermore, the enduring relationship between competitive advantage and sustainability performance in the fuzzy-set qualitative comparative analysis could validate theoretical foundations and underscore the strategic importance of sustained competitive advantage for long-term success in dynamic and competitive business environments.